PENGEMBANGAN ALAT PEMIPIL CENGKEH DI KABUPATEN KOLAKA - Yani, Akhmad; Teguh Budi Raharjo (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aimed to design and test a clove threshing machine to increase post-harvest efficiency for local farmers in Kolaka Regency. The development process involved prototype design and two phases of field testing to evaluate capacity, rotational speed, separation performance, and screening system effectiveness. In Trial 1, the machine featured a 3–5 kg hopper capacity and a low RPM, producing 1 kg of separated cloves per minute (60 kg/hour) with a separation rate of 75% clove buds and 25% stems. In Trial 2, with a 10–15 kg hopper and higher RPM, output increased to 2.5 kg per minute (150 kg/hour), with improved separation efficiency of 90% buds and only 10% stems. The screening system was also improved from a flat, non-inclined vibrating setup in Trial 1 to a 10-degree inclined fixed tray in Trial 2, further enhancing separation quality. These results demonstrate that the improved machine significantly increases productivity and separation efficiency, making it a viable appropriate technology solution for smallholder clove farmers facing labor constraints and economic shifts due to industrialization.